Herbicides to Kill Invasive Trees in Home Landscapes and Surrounding Natural Areas - Stephen F. Enloe; Kenneth A. Langeland (EDIS, 2019)
This 5-page publication discusses methods and herbicides that homeowners can readily use to remove invasive plants from landscapes and surrounding natural areas. Written by S. F. Enloe and K. A. Langeland, and published by the UF/IFAS Agronomy Department, reviewed October 2019.